2022
DOI: 10.21203/rs.3.rs-2261014/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

(2R,6R)-Hydroxynorketamine restores postsynaptic localization of AMPAR in the prelimbic cortex to provide sustained pain relief

Abstract: Neuropathic pain is a difficult-to-treat pain condition that can affect patients for years. (2R,6R)-hydroxynorketamine (R-HNK) is a ketamine metabolite without dissociative effects and has been evaluated as an alternative to ketamine in chronic pain management. The mechanism of action remains elusive. Here we report that repeated systemic or contra-prelimbic cortex (PrL) infusion of R-HNK in the acute stage of nerve injury produces sustained pain relief for at least 14 days in the mouse spared nerve injury (SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 44 publications
2
1
0
Order By: Relevance
“…5,16,19 Contrary to the studies in murine models of depression, we observed an decrease in hippocampal BDNF following (2R,6R)-HNK administration in murine models of pain. Our findings concur with those of Jin et al 10 who demonstrated using transcriptomic analysis of the prelimbic cortex that SNI pain was associated with increased BDNF signaling, abnormal dendritic spine organization, and reduced AMPAR activity and that (2R,6R)-HNK administration decreased BDNF in the prelimbic cortex when compared to saline. The authors suggested that the analgesic activity of (2R,6R)-HNK depends on modulation of the BDNF/ARC/AMPA axis possibly through reduction in BDNF (TrkB) pathway activity.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…5,16,19 Contrary to the studies in murine models of depression, we observed an decrease in hippocampal BDNF following (2R,6R)-HNK administration in murine models of pain. Our findings concur with those of Jin et al 10 who demonstrated using transcriptomic analysis of the prelimbic cortex that SNI pain was associated with increased BDNF signaling, abnormal dendritic spine organization, and reduced AMPAR activity and that (2R,6R)-HNK administration decreased BDNF in the prelimbic cortex when compared to saline. The authors suggested that the analgesic activity of (2R,6R)-HNK depends on modulation of the BDNF/ARC/AMPA axis possibly through reduction in BDNF (TrkB) pathway activity.…”
Section: Discussionsupporting
confidence: 93%
“…The authors suggested that the analgesic activity of (2R,6R)-HNK depends on modulation of the BDNF/ARC/AMPA axis possibly through reduction in BDNF (TrkB) pathway activity. 10 Our finding of a decreased ratio of BDNF in the hippocampus supports the aforementioned hypothesis.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation